Being A “Professional” LCTL At A “Professional” Level: A Call For The Inclusion Of Multiple Chinese Languages In “Chinese” Language Pedagogy - Genevieve Y. Leung; Ming-Hsuan Wu (Journal of the National Council of Less Commonly Taught Languages, 2011)
This paper examines the term “Chinese” in light of the prevalent rhetoric of Chinese as a critical language for the job market. As Mandarin has received rapid recognition and usage in “professional” contexts such as academia and international business, we call for a critical viewing of placing too much worth in the political economy of Mandarin at the expense of overlooking all the other varieties of Chinese in the local ecologies. Using data from the authors’ own experiences as instructors of Mandarin and Cantonese in secondary and university contexts, this paper speaks to the possibility of multiple Chinese languages being taught and used together, or, conversely, what the negative consequences have been in neglecting multiple varieties of Chinese in a Mandarin-only language classroom. We argue that while it is currently not the case, Mandarin can be “professional”with its fellow Chinese varieties while still being considered a LCTL used at the “professional” level.